No Sex Differences in Bone Mineral Accretion From 1 to 12 Months of Age Among a Sample of Healthy Term Breastfed Infants From Montreal, Canada. (7th June 2021) - Gharibeh, Nathalie; Gallo, Sina; Sotunde, Olusola F; Vanstone, Catherine A; Rodd, Celia J; Weiler, Hope A
Abstract: Objectives: To investigate sex differences in bone mass including whole body (WB) bone mineral content (BMC), lumbar spine (LS) BMC and LS bone mineral density (BMD) during infancy. Methods: This is a secondary analysis of data from a double-blinded randomized clinical trial (NCT00381914), in which healthy term breastfed infants were randomized to 1 of 4 doses of oral vitamin D supplementation (400−1600 IU/d) at 1 mo of age (+/− 2 wk). Serum 25-hydroxyvitamin D (25(OH)D) using liquid chromatography-tandem mass spectrometry, and BMC and BMD using dual-energy x-ray absorptiometry (Hologic) were measured at 1, 3, 6, 9, and 12 mo of age (+/- 2 wk). No effect of supplementation on BMC (WB and LS) and BMD (LS) was reported in the primary study. Infants (32 males (M), 31 females (F)) with baseline serum 25(OH)D ≥ 50 nmol/L, based on the Institute of Medicine's cutoff in support of bone health, were included in this secondary analysis. Differences between sexes over time in BMC and BMD were tested using mixed model repeated measures ANOVA accounting for the fixed effects of sex, time, and sex*time and the random effect of infant ID, with Tukey multiple comparison test. Results: Infants were on average 39.5 ± 1.1 wk gestational age, with weight for age z-score of 0.40 ± 0.97 at birth. There were no differences between sexes in mineral accretion rates of the WB (M: 12.94 ± 8.83,  F: 12.20 ± 7.71 g/mo; p = 0.36) and at the LS (M: 0.26 ± 0.28,  F: 0.22 ± 0.31 g/mo; p = 0.33) between 1 to 12 mo of age, but M had higher overall WB BMC than F (166.16 ± 57.30 vs. 153.34 ± 50.06 g,  p = 0.03). When adjusted for weight or length, no sex differences were observed over time in WB BMC per weight (M: 22.02 ± 2.29,  F: 22.20 ± 2.27 g/kg; p = 0.58) and WB BMC per length (M: 2.47 ± 0.60,  F: 2.34 ± 0.53 g/cm,  p = 0.06). Similarly, when using the WB less head BMC measurement, no sex differences were observed (M: 84.80 ± 30.24,  F: 78.41 ± 7.57 g; p = 0.07). In addition, LS BMC (M: 3.77 ± 1.34,  F: 3.75 ± 0.22 g; p = 0.93) and LS BMD (M: 0.273 ± 0.051,  F: 0.284 ± 0.054 g/m 2 ; p = 0.10) did not vary by sex. Conclusions: Sex differences in BMC in infancy, if any, are mostly driven by infant size. Based on BMC and accretion rates, sex-specific normative data do not appear required during infancy. Funding Sources: Canadian Institutes of Health Research, Nutricia Research Foundation, and the Canadian Foundation for Innovation.